BUILDING A MEASURE OF STRATEGIC READINESS FOR INSTITUTIONAL SPORTS CLUBS IN IRAQ (Neo Scientific Peer Reviewed Journal, 2023)
The research community consisted of members of the administrative bodies of the institutional sports clubs in Iraq, which numbered (47) clubs distributed throughout the governorates of Iraq, except for the Kurdistan region, and their number reached (395) members of the administrative bodies of the institutional sports clubs, and they are represented by (100%) of the research community total. The building sample included (253) members. Of the members of the administrative bodies of the institutional sports clubs in Iraq, and they were chosen by a simple random method (lottery) at a rate of (%64.05) of the total research community. (23) members were excluded because their forms were not received, and they represent (%5.82) members, to be the building sample. Consisting of (230) members, and the survey application sample, which numbered (30) members, representing (%7.59) of the research community, was excluded. Thus, the building sample consisted of (200) members, representing (%50.63) of the population. total research community.